2009
DOI: 10.1532/hsf98.20091014
|View full text |Cite
|
Sign up to set email alerts
|

Ability of B-Type Natriuretic Peptide in Predicting Postoperative Atrial Fibrillation in Patients Undergoing Coronary Artery Bypass Grafting

Abstract: Elevated preoperative BNP levels and advanced age together are significant predictors for the development of postoperative AF in patients undergoing isolated CABG with CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Advanced patient age has been repeatedly reported as an independent predictor of AF after CABG ( 1 , 2 , 17 , 18 ). Previously, many studies of postoperative AF have been done and described that predictors of postoperative AF were older age, previous history of AF, male gender, decreased left ventricular ejection fraction, valvular heart surgery, left atrial enlargement, chronic obstructive pulmonary disease, chronic renal failure, and diabetes mellitus ( 1 , 3 , 14 , 16 ).…”
Section: Discussionmentioning
confidence: 94%
“…Advanced patient age has been repeatedly reported as an independent predictor of AF after CABG ( 1 , 2 , 17 , 18 ). Previously, many studies of postoperative AF have been done and described that predictors of postoperative AF were older age, previous history of AF, male gender, decreased left ventricular ejection fraction, valvular heart surgery, left atrial enlargement, chronic obstructive pulmonary disease, chronic renal failure, and diabetes mellitus ( 1 , 3 , 14 , 16 ).…”
Section: Discussionmentioning
confidence: 94%
“…In patients undergoing pre-operative assessment, elevated baseline levels of BNP and NT-proBNP have been associated with increased risk of AF following coronary artery bypass grafting [ [23][24], cardiac surgery [ 25 ] and thoracic surgery [ 26 ]. Horie et al also found BNP predicted the development of chronic AF after pacemaker insertion in patients with sick sinus syndrome [ 27 ].…”
Section: Association Between Natriuretic Peptides and Atrial Fibrillationmentioning
confidence: 99%
“…Due to the anatomical localization of cardiac injuries, the most affected chamber is right ventricle, and than left ventricle is the second one [8]. Brathwaite et al [9] reported that left atrial injury occurs in the 25% of the cases with cardiac rupture, and atrial appendage and pulmonary vein-atrial junction are the most affected sides.…”
Section: Discussionmentioning
confidence: 99%